DIVERT for realistic simulation of heterogeneous vehicular networks - Fernandes, R (2010)
Simulation of vehicular networks has been extensively studied in the last few years. In order to have an holistic view of the network functioning, communications and vehicle mobility aspects should be modeled in detail and fully integrated. This article presents a tool for simulating heterogeneous vehicular networks. The existing microscopic traffic simulator, DIVERT, has been extended by adding NS-3 support resulting in a very tightly integrated simulator. The feasibility of the approach has been tested by means of an application example: in-vehicle traffic lights. The provided results demonstrate the superior performance and the scalability of this novel simulator. (c)2010 IEEE.